Ketum (Mitragyna Speciosa Korth.) Consumption, Lipid Profile And Electrocardiogram (Ecg) Abnormalities - Korindasamy, Novline Yuvashnee (2023)
Ketum (Mitragyna speciosa Korth.) a native medicinal plant of Southeast Asia, has been used in Malaysia for decades for its unique curative properties. Given its broad therapeutic properties and increasing utility, ketum’s long-term safety profile, especially on its cardiotoxicity risk remains poorly investigated in regular ketum users. Given this research limitation, this study aims to evaluate the electrocardiogram (ECG) abnormalities and lipid profile between regular ketum users and healthy control subjects. A total of 200 respondents (n=100 regular ketum users and n=100 healthy control subjects) were recruited through convenience sampling from the northern peninsular state of Penang for this clinical, cross-sectional study. All were required to undergo an ECG evaluation, and blood samples were also drawn to characterize the respondent’s lipid profile. All males, a majority were Malays (97%, n=194/200), and the samples mean age in this study was 33 years (SD=6.7), while ketum users mean duration of ketum use was 6.4 years (SD=4.31). Ketum users mean systolic and diastolic blood pressure rates were 132.9 beats per minute (SD=17.3) and 77.1 beats per minute (SD=11.1), respectively.